2022
DOI: 10.3390/rs14061439
|View full text |Cite
|
Sign up to set email alerts
|

DIC-ST: A Hybrid Prediction Framework Based on Causal Structure Learning for Cellular Traffic and Its Application in Urban Computing

Abstract: The development of technology has strongly affected regional urbanization. With development of mobile communication technology, intelligent devices have become increasingly widely used in people’s lives. The application of big data in urban computing is multidimensional; it has been involved in different fields, such as urban planning, network optimization, intelligent transportation, energy consumption and so on. Data analysis becomes particularly important for wireless networks. In this paper, a method for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…With the ongoing progress of technology, the utilization of support vector machines (SVMs) and K-nearest neighbors (KNNs) has become widespread in the domain of cellular network traffic prediction [19,20]. These models convert the prediction problem into a linear partition problem, reducing the artificial impact on prediction results and enhancing the prediction accuracy to a certain degree.…”
Section: Related Workmentioning
confidence: 99%
“…With the ongoing progress of technology, the utilization of support vector machines (SVMs) and K-nearest neighbors (KNNs) has become widespread in the domain of cellular network traffic prediction [19,20]. These models convert the prediction problem into a linear partition problem, reducing the artificial impact on prediction results and enhancing the prediction accuracy to a certain degree.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, different types of time series data have different requirements for the length of the time series used to calculate the TE. For example, a study by Zhang et al [49] found that for different components of the same time series, the causal relationships between them differed in nature.…”
Section: Determination Of the Parameters For Transfer Entropymentioning
confidence: 99%
“…From the figure, it is evident that the time series data of largescale industrial systems, as represented by the satellite, exhibits significant periodicity. Therefore we choose an integer multiple of time series data period as the total length of the time series data for estimating the TE, drawing on the study by Zhang et al [49].…”
Section: Determination Of the Parameters For Transfer Entropymentioning
confidence: 99%